The Indonesian Financial System : Its Contribution to Economic Performance, and Key Policy Issues - Montgomery, John (IMF Working Papers; Working Paper, 1997)
The structure of the financial system in Indonesia is examined through the analytical lens of the system's contribution to the growth, stability, and efficiency of the Indonesian economy. The focus is on the banking system and securities markets, which are the primary mechanisms for mobilizing savings and allocating investment funds. Five key policy issues are highlighted: (1) the level of bank capitalization; (2) the supervision and regulation of banks; (3) the structure of banking markets; (4) the deepening of securities markets; and (5) the supervision and regulation of securities markets.